Comparison of the Relative Diagnostic Performance of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT for the Detection of Bone Metastasis in Patients With Different Cancers - Junhao Wu; Junhao Wu; Junhao Wu; Yingwei Wang; Yingwei Wang; Yingwei Wang; Taiping Liao; Taiping Liao; Taiping Liao; Zijuan Rao; Zijuan Rao; Zijuan Rao; et al. (Frontiers in Oncology, 2021)
PurposeThe present retrospective analysis sought to compare the relative diagnostic efficacy of [68Ga]Ga-DOTA-FAPI-04 to that of [18F]FDG PET/CT as a means of detecting bone metastases in patients with a range of cancer types.MaterialsIn total, 30 patients with bone metastases associated with different underlying malignancies were retrospectively enrolled. All patients had undergone [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT, and the McNemar test was used to compare the relative diagnostic performance of these two imaging modalities. The maximum standard uptake value (SUVmax) was used to quantify radiotracer uptake by metastatic lesions, with the relative uptake associated with these two imaging strategies being compared via the Mann-Whitney U test. The cohort was further respectively divided into two (osteolytic and osteoblastic bone metastases) and three clinical subgroups (lung cancer, thyroid cancer, and liver cancer).Results[68Ga]Ga-DOTA-FAPI-04 PET/CT was found to be significantly more sensitive as a means of diagnosing bone metastases relative to [18F]FDG PET/CT ([109/109] 100% vs [89/109] 81.7%; P< 0.01), consistent with the significantly increased uptake of [68Ga]Ga-DOTA-FAPI-04 by these metastatic lesions relative to that of [18F]FDG (n=109, median SUVmax, 9.1 vs. 4.5; P< 0.01). [68Ga]Ga-DOTA-FAPI-04 accumulation was significantly higher than that of [18F]FDG in both osteolytic (n=66, median SUVmax, 10.6 vs 6.1; P < 0.01), and osteoblastic metastases (n=43, median SUVmax, 7.7 vs 3.7; P < 0.01). [68Ga]Ga-DOTA-FAPI-04 uptakes were significantly higher than that of [18F]FDG in bone metastases from lung cancer (n = 62, median SUVmax, 10.7 vs 5.2; P < 0.01), thyroid cancer (n = 18, median SUVmax, 5.65 vs 2.1; P < 0.01) and liver cancer (n = 12, median SUVmax, 5.65 vs 3.05; P < 0.01). However, [68Ga]Ga-DOTA-FAPI-04 detected 10 false-positive lesions, while only 5 false-positive were visualized by [18F]FDG PET/CT.Conclusion[68Ga]Ga-DOTA-FAPI-04 PET/CT exhibits excellent diagnostic performance as a means of detecting bone metastases, and is superior to [18F]FDG PET/CT in this diagnostic context. Furthermore, [68Ga]Ga-DOTA-FAPI-04 tracer uptake levels are higher than those of [18F]FDG for most bone metastases. However, owing to the potential for false-positive bone lesions, it is critical that physicians interpret all CT findings with caution to ensure diagnostic accuracy.